Demethylation of dimethylsulfoniopropionate to 3-mercaptopropionate by an aerobic marine bacterium. - Visscher, P T (1994)
A bacterium, strain BIS-6, that grew aerobically on dimethylsulfoniopropionate (DMSP) was isolated from an intertidal mud sample. Strain BIS-6 quantitatively demethylated DMSP and 3-methiolpropionate to 3-mercaptopropionate. Strain BIS-6 was a versatile methylotroph growing on the osmolytes DMSP and glycine betaine and their methylated degradation products (dimethyl glycine, sarcosine, methylamines, and dimethyl sulfide.